A new jump-landing protocol identifies differences in healthy, coper, and unstable ankles in collegiate athletes - Liu, K.; Dierkes, C.; Blair, L. (Sports Biomechanics, 2016)
Ankle sprains are the most common injury in sport. With stability being an important risk factor for ankle sprains, a jump-landing protocol that can elicit differences in time-to-stabilisation (TTS) is necessary. The objective of this study was to develop a jump-landing protocol that could identify differences in TTS among healthy, coper, and unstable ankles of high-level athletes. 61 Division I collegiate athletes (32 females, 29 males; age: 19.9±1.2 years; height: 176.6±9.5cm; mass: 74.3±10.8kg) participated in a jump-landing protocol that utilised sporting movements with preparatory steps and a vertical propulsion of the body in two multi-directional jumps. Utilising the landing on a force plate, ground reaction forces were used to quantify TTS. TTS of the unstable group (1.58±0.62s) was significantly longer than the healthy (1.19±0.37s; p=0.050) and coper (1.13±0.49s; p=0.019) groups in the forward hops. In addition, TTS of the lateral hops in the unstable group (1.55±0.63s) was also significantly longer than the healthy (1.14±0.37s; p=0.026) and coper (1.15±0.39s; p=0.028) groups. This new jump-landing protocol was able to elicit differences in TTS in high-level athletes that were not found using previous protocols. This new jump-landing protocol could be an effective tool to identify injury risk for high-level athletes.